Fluidized Hot Melt Granulation Technique: An Approach to Improve Micromeritics Properties and Dissolution Rate of Efavirenz (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The Fluidized hot melt granulation technique is a process by which pharmaceutical powders are efficiently agglomerated using a low melting binder. The effect of the binder properties and concentrations on agglomerate growth mechanisms were studied in this research paper using this technique with the primary objective of improvement in the solubility and dissolution rate of efavirenz by melt-dispersion granulation employing meltable hydrophilic carrier and then to convert the melt dispersion into flowable and compressible dispersion granules to yield a rapidly dissolving tablet formulation. The Optimized concentrations of co-polymers like PEG 6000, PEG 4000, Gelucire 50/13, Gelucire 44/14, Poloxamer 188 and Poloxamer 407 in different ratios (i.e., 1:1, 1:2, 1:3 and 1:4) as meltable binder along with the drug were sprayed dropwise over lactose as diluent loaded into fluid bed chamber for the preparation of the granules of efavirenz and characterized for its micromeritical properties, DSC, XRD etc. The tablets prepared from the granules were evaluated for drug dissolution rate. The prepared granules were found to have excellent flow properties indicated by mean diameter D50:138µm, Carr’s index 13.92% and the drug content uniformity of 98.10%. XRD data exhibited partial loss of crystallinity as indicated by significantly less intensity of efavirenz peak in sample than pure efavirenz. Drug release from tablet was fast found 99.12% w/v within 30 minutes. Absence of Efavirenz endothermic peak at higher proportions of meltable binder reported by DSC data exhibited amorphous form of efavirenz led to complete solubilization and thus faster dissolution rate of efavirenz.